ANALISIS USER EXPERIENCE WEBSITE PRESMA UPNVJ MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) DAN SINGLE EASE QUESTION (SEQ) PADA MAHASISWA AKTIF UPN "VETERAN" JAKARTA ANGKATAN 2019 DAN 2020 - Tazkia Hanifah Susilo (2023)
Presma UPNVJ is a website-based information system created and developed by UPT TIK UPN "Veteran" Jakarta. This information system serves as a data collection system related to achievements, activities, organizations, and certification of expertise used by UPN "Veteran" Jakarta students during their active enrolment. The data will later be included in the Sertifikat Keterangan Pendamping Ijazah (SKPI). The existence of the Presma UPNVJ website aims to facilitate the process of recording achievements, requiring the system to be user-friendly, taking into account the user experience. Therefore, an analysis of the website's usability level is necessary. The method used in this research is the System Usability Scale (SUS) in the form of a questionnaire involving 380 respondents to measure the overall usability level of the Presma UPNVJ website. Additionally, scenario-based task testing was conducted using usability metrics attributes and the Single Ease Question (SEQ) method with 7 respondents. The research findings revealed 12 usability problems categorized into 4 UX Elements: Branding, Usability, Functionality, and Content. Recommendations for design improvements are based on the grouping of UX Elements to enhance user ease and efficiency in interacting with the system. These recommendations can be used by the UPT TIK UPN "Veteran" Jakarta to improve the usability level and user experience of the Presma UPNVJ website